River Stage Variability and Extremes in the Itacaiúnas Basin in the Eastern Amazon: Machine Learning-Based Modeling - Luiz Rodolfo Reis Costa; Douglas Batista da Silva Ferreira; Renato Cruz Senna; Adriano Marlisom Leão de Sousa; Alexandre Melo Casseb do Carmo; João de Athaydes Silva; Felipe Gouvea de Souza; Everaldo Barreiros de Souza (Hydrology)
This study fosters tropical hydroclimatology research by implementing a computational modeling framework based on artificial neural networks and machine learning techniques. We evaluated two models, Multilayer Perceptron (MLP) and Support Vector Machine (SVM), in their ability to simulate 20-year monthly time series (2001–2021) of minimum and maximum river stage in the Itacaiúnas River Basin (BHRI), located in the eastern Brazilian Amazon. The models were configured using explanatory variables spanning meteorological, climatological, and environmental dimensions, ensuring representation of key local and regional hydrological drivers. Both models exhibited robust performance in capturing fluviometric variability, with a comprehensive multimetric statistical evaluation indicating MLP’s superior accuracy over SVM. Notably, the MLP model reproduced the maximum river level during a sequence of extreme hydrological events linked to natural disasters (floods) across BHRI municipalities. These findings underscore the computational model’s potential for refining hydrometeorological products, thus supporting water resource management and decision-making processes in the Amazon region.